Squamous cell carcinoma in Hand – Case report Carcinoma de células escamosas na mão - Estudo de caso - Silva, Joaquim José de Lima; Lima, Antonia Artemisa Aurélio Soares; Melo, Juliana Oliveira; Valdívia, Paulo; Machado, July (Journal of Health & Biological Sciences, 2016)
Introduction: Squamous cell carcinoma (SCC) is a type of skin malignancy that originates in the squamous layer of the epidermis. A lower incidence than basal cell carcinomas is reported. There is a predominance of areas heavily exposed to sunlight Objectives: To report a case of squamous cell carcinoma in left hand compromising the hypothenar region. To carry out a literature review and emphasize the main methods of diagnosis and treatment. Methods: Information obtained from medical records, photographic record of pre and post-operative. Result: Histopathological diagnosis was made, confirming squamous cell carcinoma due to the evolution of metastatic basal cell carcinoma, with the removal of bones: 5th metacarpal and scaphoid. After relapse, requiring amputation of the left hand. Conclusion: To report a rare case of bone metastasis derived from a skin cancer.